Ethical Analysis of Software Piracy in the Context of Information Technology: Impacts on Intellectual Property Rights, Copyright Holders, and Users - AYU NOVITASARI (Institute of Information Technology and Social Science (IITSS), 2023)
Software piracy has emerged as a critical ethical concern in the digital era, challenging the principles of intellectual property and innovation. This study aims to explore the ethical dimensions of software piracy and analyze its implications for copyright holders, consumers, and society. Utilizing a systematic literature review, this paper investigates legal frameworks, moral consequences, and ethical dilemmas associated with software piracy. Findings reveal that piracy undermines both the moral and economic rights of creators, leading to extensive financial losses and heightened cybersecurity risks. The study emphasizes the need for ethical education, stronger legal enforcement, and digital literacy initiatives to mitigate software piracy. This paper contributes to the understanding of ethical issues in digital innovation and proposes strategies to enhance compliance and integrity in software usage.